2014
DOI: 10.1093/carcin/bgu124
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Targeting the Warburg effect with a novel glucose transporter inhibitor to overcome gemcitabine resistance in pancreatic cancer cells

Abstract: Gemcitabine resistance remains a significant clinical challenge. Here, we used a novel glucose transporter (Glut) inhibitor, CG-5, as a proof-of-concept compound to investigate the therapeutic utility of targeting the Warburg effect to overcome gemcitabine resistance in pancreatic cancer. The effects of gemcitabine and/or CG-5 on viability, survival, glucose uptake and DNA damage were evaluated in gemcitabine-sensitive and gemcitabine-resistant pancreatic cancer cell lines. Mechanistic studies were conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 47 publications
3
26
0
Order By: Relevance
“…4b,c). Consistent with previously published reports293034, ChIP analysis confirmed the binding of E2F1 to RRM2 promoter (Fig. 4d) and its knockdown significantly reduced BRCA1 recruitment to promoter regions amplified by both primer sets (P1 and P2), thereby indicating that BRCA1 binding and transcriptional activation of RRM2 occurs in E2F1-dependent manner (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…4b,c). Consistent with previously published reports293034, ChIP analysis confirmed the binding of E2F1 to RRM2 promoter (Fig. 4d) and its knockdown significantly reduced BRCA1 recruitment to promoter regions amplified by both primer sets (P1 and P2), thereby indicating that BRCA1 binding and transcriptional activation of RRM2 occurs in E2F1-dependent manner (Fig.…”
Section: Resultssupporting
confidence: 92%
“…3a and Table 1). To test the involvement of BRCA1 in the recovery of stalled replication forks, we monitored the stability of nascent replication tracts29 post exposure to exogenous RS (2 mM hydroxyurea (HU) for 4 h). Specifically, nascent replication tracts were CldU-labelled after replication stalling with HU.…”
Section: Resultsmentioning
confidence: 99%
“…Apigenin, a flavonoid drug, exhibits antiproliferative properties in pancreatic cancer by decreasing glucose uptake and downregulating GLUT-1 in human pancreatic cancer cells [42]. Given that gemcitabine is the mainstay of treatment in pancreatic cancer and its resistance remains a serious clinical challenge to treatment, a recent study showed that targeting the Warburg effect with a novel GLUT inhibitor, CG-5, in combination with gemcitabine caused greater suppression of Panc-1 xenograft tumor growth in vivo than either drug alone [43]. This occurs via CG-5 restoring the sensitivity of drug-resistant Panc-1 cells to gemcitabine by abrogating the effect of gemcitabine by targeting the upregulation of gemcitabine-induced expression of ribonucleotide reductase M2 catalytic subunits to overcome drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The synergism with gemcitabine was demonstrated also in vivo : the co-administration of the two drugs reduced tumour growth to a greater extent than the treatment with the two compounds alone, without any evident signs of toxicity in treated mice. 67 …”
Section: Synthetic Glut Inhibitorsmentioning
confidence: 99%